Pemikiran Sartono Kartodirdjo Tentang Sejarah Perkotaan - Basundoro, Purnawan (Jurnal Sejarah Indonesia, 2024)
This article explores Sartono Kartodirdjo's views regarding urban studies in Indonesia, especially his opinions regarding cities. This paper was written using library research methods. The library material used as a reference for this writing is various literature by Sartono Kartodirdjo which reflects his thoughts, especially those that discuss urban areas. Sartono showed sufficient enthusiasm in seeing the city as a historical study unit, positioning the city as a center of modernization. The main instruments of modernization in urban areas are means of communication, education, and newspapers or mass media. Modernization in urban areas has brought Indonesia towards the door of independence due to the emergence of a new awareness among the educated elite in urban areas. In this way, cities contribute and play an important role in Indonesian history, at least from Sartono Kartodirdjo's academic perspective.